Reduced primary T lymphopoiesis in 3-month-old lurcher mice: sign of premature ageing of thymus? - Mandakova, Petra; Sinkora, Jiri; Sima, Petr; Vozeh, Frantisek (Neuroimmunomodulation, 2005)
OBJECTIVE: The nervous, endocrine and immune systems are functionally interconnected so that they may form a complex metasystem. Abnormalities within the neuroendocrine compartment can thus affect immune mechanisms and vice versa. The Lurcher-type mutation in mice has a profound impact on brain development in both homozygous and heterozygous individuals, which is followed by immune system changes. We investigated whether macroscopic changes in the thymus size were associated with an altered thymocyte development or with changes in peripheral T cell subset distribution. METHODS: CD3, CD4 and CD8 expressions on thymocytes and peripheral T cells were compared with those in wild-type and Lurcher heterozygous C3H mice using surface immunophenotyping and flow cytometry. Galanthus nivalis agglutinin binding to thymocytes was measured at the same time. RESULTS: While no differences between experimental groups were observed in 1-month-old mice, a critical reduction of numbers of thymocytes and namely double-positive cells occurred before the age of 3 months in Lurcher mice, which was accompanied by thymus involution. Interestingly, this was not accompanied by significant differences in major T subset proportions in the peripheral lymphatic tissue. CONCLUSIONS: We interpret our observations as hallmarks of premature thymus ageing in heterozygous Lurcher mice with only a marginal effect in the periphery in early adulthood.
Keywords: CD3 Complex; T-Lymphocyte Subsets; Aging; Mice, Neurologic Mutants; antigeny CD8; CD8 Antigens; Thymus Gland; antigeny CD3; imunohistochemie; thymus; myši - mutanty neurologické; T-lymfocyty - podskupiny; Flow Cytometry; T-lymfocyty; CD4 Antigens; antigeny CD4; průtoková cytometrie; Animals; ženské pohlaví; Immunohistochemistry; zvířata; stárnutí; Lymphopoiesis; myši; T-Lymphocytes; Mice; Female; lymfopoéza